Insulin Therapy- Common Misconceptions among Diabetics - Saira Gul , Mudassir Abbas , Zainab Amjad , Muhammad Mudassir Shafiq , Wajeeha Shafiq, Saira Gul , Mudassir Abbas , Zainab Amjad , Muhammad Mudassir Shafiq , Wajeeha Shafiq (Journal of Rawalpindi Medical College, 2017)
Abstract Background: To find out misconceptions about insulin among diabetics presenting in outpatient department of a tertiary care hospital. Methods: in this cross-sectional observational study, diabetic patients either male or female, more than 15 year of age, irrespective of their diabetes typing were included. Patient less than 15 year of age, having dementia, having other mental or psychiatric illness were not included. The sampling technique was non probability random sampling . The study tool was a predesigned questionnaire, containing close-ended questions. . Results: Out of 250 respondents,50% were male. About 69% responded that insulin commencement means serious stage of diabetes and 68% considered as an expensive modality . According to 32% insulin usage restricts daily life activities. Conclusion: Diabetic patients of this area had many misconceptions about the insulin therap